Laboratory Diagnosis of Chlamydia Pneumoniae Infections - Rosanna W Peeling (Canadian Journal of Infectious Diseases)
Chlamydia pneumoniae is an important cause of respiratory illness. There is a need for accurate and rapid laboratory diagnostic methods that will lead to improved patient care, appropriate use of antimicrobial therapy and a better understanding of the epidemiology of this emerging pathogen. Culture is highly specific but is technically demanding, expensive, has a long turnaround time and its sensitivity is highly dependent on transport conditions. Antigen detection tests such as enzyme immunoassay and direct fluorescent antibody assay, and molecular detection methods such as the polymerase chain reaction assay, may provide a rapid diagnosis without the requirement for stringent transport conditions. The results of these tests should be interpreted with caution until more thorough evaluation is available. Serology remains the method of choice. The limitations of different serological methods for the laboratory diagnosis of C pneumoniae are discussed.